Budaya Parodo (Kawin Paksa) di Sumba dan Imoralitas - Kelen, Konradus Doni; Kami, Kanisius; Gena, Engel Bertha H.; Ina, Santi Nona (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This research begins of a sense of concern for the fate of women who are held hostage by parodo marriage culture, a very immoral patriarchal culture. The aim of this research is to show the immorality of parodo culture for women, and the importance of respecting the woman's human rights. The method used in this research is ethnography with a qualitative descriptive approach. The results of this research show that the practice of parodo culture is actually very unfair, immoral and degrading women's dignity. The data in this research was obtained from field studies, observations and interviews. It is hoped that the results of this research can be used as evaluation material for the people of Sumba to immediately stop the very immoral practice of parodo culture.